A Multicultural Portrait of the Civil War - Piggins, Carol Ann (Marshall Cavendish Corporation, 1994)
Portrays the American Civil War and Reconstruction from the vantage point of ethnic minorities and women, especially African Americans.
Keywords: Juvenile literature-History-Civil War (1861 to 1865)-Social life and customs-Afro Americans-Social sciences-Minorities-United States-Nonfiction